Meningkatkan Minat Mencuci Tangan Pada Anak Usia 3-4 Tahun Menggunakan Jalur Berpola - Chusna, Nazilatul (Jurnal Penelitian Anak Usia Dini, 2024)
This study aims to determine the increase in interest in washing hands using patterned paths in children aged 3-4 years. By taking research subjects, namely 7 children with an age classification of 3-4 years at PAUD Griya Ananda Karangploso. This research uses a quantitative method with an exploratory descriptive approach, because the results of this research will be analyzed descriptively and by displaying calculated tables or graphs. The data collection technique used is in the form of a checklist sheet and documentation, as well as the data analysis technique used is using a proportional formula to convert the increase in children's interest.Based on the results of research carried out by researchers, it was concluded that the interest in washing hands of children in this study was in the low category, most children aged 3-4 years received low scores. Hand washing activities in playgroup classes were carried out every day with the help of class A or class B, which causes no own initiative to wash your hands when the time comes. This makes researchers use play media as a tool to increase interest in hand washing in playgroup classes. However, after being given play media, namely patterned paths, there was an increase in interest in washing hands using patterned paths for each child which can be seen in the research results. The research results showed that most children experienced an increase from the BB (Not Developing) category on the first day and then experienced an increase to the BSB (very well developed) category. It can be concluded that the use of play media, namely patterned paths, can make it easier for children to get to the hand washing place, is an effective method, is a safe media to use, and is easy for children to use to increase interest in washing hands in children aged 3-4 years.